PENGARUH PEMBERIAN AIR REBUSAN DAUN ALPUKAT TERHADAP PENURUNAN TEKANAN DARAH PADA WANITA MENOPAUSE DENGAN HIPETENSI DI WILAYAH KERJA PUSKESMAS DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Sari, Husna; Hayati, Erlina; Krisna, Putri; Putri Hidayat, Raysa Aulia (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Menopause is a natural phase experienced by women, where in this phase women no longer experience menstruation. This is caused by the hormones estrogen and progesterone in a woman's body decreasing so that the ovaries stop releasing eggs. Many women are worried and afraid of facing menopause because they have entered old age and cannot give birth to more children. This change in hormonal balance can cause various psychological symptoms characterized by irritability, depression, anxiety, erratic mood, decreased ability to think and memory and causes blood pressure to increase. Quercetin and flavonoids found in avocado leaves have blood pressure-lowering properties. In 2024, the study was done at the Deli Tua Health Centre in the Deli Tua Subdistrict of the Deli Serdang Regency. The goal was to find out if giving menopausal women with high blood pressure boiling avocado leaf water could lower their blood pressure. One group took a pre- and post-test as part of this type of study, which was kind of like an experiment. The chi-square test for bivariate analysis showed that the p-value was 0.000, which is less than 0.05. This means that boiling avocado leaf water does have a significant effect on lowering blood pressure.